6y+7+3y=3(3y-2)+13

Simple and best practice solution for 6y+7+3y=3(3y-2)+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+7+3y=3(3y-2)+13 equation:


Simplifying
6y + 7 + 3y = 3(3y + -2) + 13

Reorder the terms:
7 + 6y + 3y = 3(3y + -2) + 13

Combine like terms: 6y + 3y = 9y
7 + 9y = 3(3y + -2) + 13

Reorder the terms:
7 + 9y = 3(-2 + 3y) + 13
7 + 9y = (-2 * 3 + 3y * 3) + 13
7 + 9y = (-6 + 9y) + 13

Reorder the terms:
7 + 9y = -6 + 13 + 9y

Combine like terms: -6 + 13 = 7
7 + 9y = 7 + 9y

Add '-7' to each side of the equation.
7 + -7 + 9y = 7 + -7 + 9y

Combine like terms: 7 + -7 = 0
0 + 9y = 7 + -7 + 9y
9y = 7 + -7 + 9y

Combine like terms: 7 + -7 = 0
9y = 0 + 9y
9y = 9y

Add '-9y' to each side of the equation.
9y + -9y = 9y + -9y

Combine like terms: 9y + -9y = 0
0 = 9y + -9y

Combine like terms: 9y + -9y = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 7x+7=4x-20 | | (8x-8)2-25=0 | | 6y+7+3y=3 | | x-5+x+.75x+.25x+3=360 | | 3t+7=-2t+27 | | y=-.5(4)-3 | | 6+-5x=-30 | | 16x+7=15+15x | | x-5+x+.75x+.25x+3=180 | | 7-4x-4(x-2)=-1 | | 9-2(x+3)=3 | | (98)x=6272 | | 2x-27=-15 | | 1.75c=7.5 | | 13y+19=6(9+1y)+18 | | y=-.5(2)-3 | | x^2-28x=-49 | | x+102=4*x | | 4-2(5-2x)=9-6x | | m^3-4m^2+5m-1=0 | | y=-.5(-2)-3 | | 3n/5=-20 | | 6+12x=112+3x+2 | | y=-.5(-4)-3 | | B+10=-5 | | 3.7y(-4.5y)(-0.1y)= | | 65y=4(16y+110) | | 7-13x-5-8x=5 | | -1+f/2=-1 | | 20-n=40 | | 5(v+5)+2v=3 | | 200x+180y=2240 |

Equations solver categories